Transforming early childhood education in Saudi Arabia: AI’s impact on emotional recognition and personalized learning - Aldhilan, Dalal; Rafiq, Shahid (Institute of Advanced Engineering and Science, 2025)
Artificial intelligence (AI) technologies are increasingly integrated into early childhood education (ECE) worldwide, promising to revolutionize learning experiences for young children. ECE in Saudi Arabia faces challenges in addressing diverse learning needs and fostering socio-emotional development. This qualitative study investigates the role of AI in enhancing emotional recognition, promoting socio-emotional development, and addressing associated challenges in the context of Saudi Arabian schools. A total of 55 ECE teachers in Jeddah were interviewed using purposive sampling, with data saturation achieved at 50 interviews. Themes emerging from the data highlight AI’s effectiveness in personalizing learning experiences based on individual needs and learning styles, fostering empathy and social interaction among children, and enhancing classroom management. Challenges identified include data privacy concerns, cultural adaptation of AI tools, and ensuring equitable access to technology. The study highlights the importance of comprehensive teacher training, ethical guidelines, and robust policy frameworks to support responsible AI integration in Saudi Arabian education. Implications for practice include enhancing educational practices through AI while emphasizing the human role of educators, and the need for ongoing research to inform future innovations in ECE.